2018
DOI: 10.1186/s13045-018-0645-x
|View full text |Cite
|
Sign up to set email alerts
|

The roles of metallothioneins in carcinogenesis

Abstract: Metallothioneins (MTs) are small cysteine-rich proteins that play important roles in metal homeostasis and protection against heavy metal toxicity, DNA damage, and oxidative stress. In humans, MTs have four main isoforms (MT1, MT2, MT3, and MT4) that are encoded by genes located on chromosome 16q13. MT1 comprises eight known functional (sub)isoforms (MT1A, MT1B, MT1E, MT1F, MT1G, MT1H, MT1M, and MT1X). Emerging evidence shows that MTs play a pivotal role in tumor formation, progression, and drug resistance. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
271
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(282 citation statements)
references
References 208 publications
(194 reference statements)
5
271
0
6
Order By: Relevance
“…Metallothionein (MT) is a unique cysteine‐rich small protein, which plays an important role in maintaining steady‐state levels and detoxification of metal ions (Albrecht et al, ; Coyle, Philcox, Carey, & Rofe, ). In addition, recent experimental evidence suggests that MTs play a key role in tumorigenesis, development, drug resistance, and metastasis by participating in a variety of biological processes (Si & Lang, ). As a major member of the MT family, low expression of MT1M is related to poor prognosis in large cell lung cancer, esophageal squamous cancer, and hepatocellular carcinoma (da Motta, De Bastiani, Stapenhorst, & Klamt, ; Ding & Lu, ; Oka et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metallothionein (MT) is a unique cysteine‐rich small protein, which plays an important role in maintaining steady‐state levels and detoxification of metal ions (Albrecht et al, ; Coyle, Philcox, Carey, & Rofe, ). In addition, recent experimental evidence suggests that MTs play a key role in tumorigenesis, development, drug resistance, and metastasis by participating in a variety of biological processes (Si & Lang, ). As a major member of the MT family, low expression of MT1M is related to poor prognosis in large cell lung cancer, esophageal squamous cancer, and hepatocellular carcinoma (da Motta, De Bastiani, Stapenhorst, & Klamt, ; Ding & Lu, ; Oka et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Metallothionein (MT) is a unique cysteine-rich small protein, which plays an important role in maintaining steady-state levels and detoxification of metal ions (Albrecht et al, 2008;Coyle, Philcox, Carey, & Rofe, 2002). In addition, recent experimental evidence suggests that MTs play a key role in tumorigenesis, development, drug resistance, and metastasis by participating in a variety of biological processes (Si & Lang, 2018). et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were consistent with our previous study (Zhang et al, ), in which no significant lipid accumulation was observed after subchronic Cd exposure, although the mRNA level of genes associated to hepatic lipid metabolism was elevated in adult female mice. Mt, the metal‐binding proteins and the most responsive proteins to Cd exposure, are small cysteine‐rich proteins that play important roles in metal homeostasis and protection against heavy metal toxicity, DNA damage and oxidative stress (Si & Lang, ). In a mouse model of Cd‐induced FGR, Mt1 and Mt2 , two Mt genes, were upregulated in maternal liver.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transforming growth factor (TGF)-β also plays a crucial role during the cell proliferation (Muraoka et al, 2002;Schiller, rich proteins that play important roles in metal homeostasis and protection against heavy metal toxicity, DNA damage and oxidative stress (Si & Lang, 2018). In a mouse model of Cd-induced FGR, Mt1 and Mt2, two Mt genes, were upregulated in maternal liver.…”
Section: Discussionmentioning
confidence: 99%
“…9B). Metallothioneins are a family of small proteins that play important roles in metal homeostasis and protection against heavy metal toxicity, DNA damage and oxidative stress (Si and Lang, 2018). Their induction in tumor-associated macrophages (TAMs) has been noted (Ge et al, 2012) but to our knowledge this is the first report of an association with clinical outcome.…”
Section: In-depth Evaluation Of the Sade-feldman Et Al Immunotherapymentioning
confidence: 97%